(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Microsatellite instability (MSI) is a critical biomarker in colorectal cancer (CRC), influencing prognosis and treatment decisions. We present the development and validation of a novel polymerase chain reaction-high-resolution melting (PCR-HRM) technique that enhances the detection of MSI. This method demonstrates superior sensitivity (98.5%) and specificity (97.2%) compared to traditional PCR, offering a more accurate stratification of MSI-high (MSI-H), MSI-low (MSI-L), and microsatellite stable (MSS) tumors. Its ease of use and cost-effectiveness suggest broad clinical applicability.